2020
DOI: 10.1055/a-1157-8611
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of gastroesophageal variceal bleeding after oxaliplatin-based chemotherapy in patients with colorectal cancer

Abstract: Background Oxaliplatin, used as first-choice treatment for colorectal cancer (CRC), induces sinusoidal endothelial injury and portal hypertension. This study investigated the characteristics of oxaliplatin-induced portal hypertension and evaluated the efficacy of endoscopic management of gastroesophageal variceal bleeding. Methods We performed a retrospective, multicenter, case-control study between January 2010 and December 2018. Patients who received oxaliplatin-based chemotherapy after CRC surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
2
6
0
Order By: Relevance
“…In the EGV group, there were no obvious changes in biochemical signs of liver damage, such as AST, ALT and total bilirubin. Huang and colleagues suggested that oxaliplatin-related portal hypertension is characterized by massive ascites, splenomegaly, gastric varices, concomitant arterioportal stula, and relatively normal liver function [11]. This report supported our data, together indicating that the absence of signs of liver damage could delay the detection of EGV.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the EGV group, there were no obvious changes in biochemical signs of liver damage, such as AST, ALT and total bilirubin. Huang and colleagues suggested that oxaliplatin-related portal hypertension is characterized by massive ascites, splenomegaly, gastric varices, concomitant arterioportal stula, and relatively normal liver function [11]. This report supported our data, together indicating that the absence of signs of liver damage could delay the detection of EGV.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has also become widely known that oxaliplatin may lead to the development of portal hypertension and esophagogastric varices (EGV). Some case reports, including from our group, have shown that EGV formation or rupture during or after oxaliplatin-containing chemotherapy can make it di cult to continue the treatment and may worsen the prognosis [8][9][10][11][12]. However the prevalence of and risk for developing EGV after oxaliplatin treatment is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and colleagues suggested that oxaliplatin-related portal hypertension is characterized by massive ascites, splenomegaly, gastric varices, concomitant arterio-portal fistula, and relatively normal liver function. 11 This report supported our data, indicating that the absence of signs of liver damage could delay the detection of EGVs. Therefore, it is important to assess changes in platelet counts and spleen size on CT scan in patients treated with oxaliplatin-based chemotherapy.…”
Section: Presupporting
confidence: 90%
“…Some case reports, including from our group, have shown that EGV formation or rupture during or after oxaliplatincontaining chemotherapy can make it difficult to continue the treatment and may worsen the prognosis. [8][9][10][11][12] However, the prevalence of and risk for developing EGVs after oxaliplatin treatment are unclear. We therefore evaluated clinical features predictive of the development of EGVs in colorectal cancer patients treated with oxaliplatin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Ligation and cyanoacrylate glue injection under gastroscopy are the first-line treatment options for esophageal and gastric variceal bleeding in liver cirrhosis[ 17 ], but whether they are appropriate for esophageal and gastric variceal bleeding related to NCPH remains controversial. A previous study reported that the effect of endoscopic therapy in preventing variceal rebleeding in patients with NCPH is not ideal, compared to its effect in preventing hepatitis B cirrhosis-related portal hypertension[ 18 ]. Due to good functional liver reserve in patients with NCPH, transjugular intrahepatic portosystemic shunt (TIPS) treatment has a lower rebleeding rate, and the incidence and mortality of postoperative hepatic encephalopathy are lower[ 19 ].…”
Section: Discussionmentioning
confidence: 99%